The Influence of Intention To Use Digital Wallet Applications, E-Service Quality And Trust on Consumer Satisfaction Toward Digital Payment Applications - Apriliani, Rina; Prakoso, Teguh; Rustaman, Dede; Dharmawan, Donny; Wildan Nuryanto, Uli (SEULANGA SYSTEM PUBLISHER, 2024)
This research aims to see whether there is an influence between electronic service quality and trust on the decision to use electronic money services and its impact on consumer satisfaction. The population in this study is all people who use electronic money. This study's sample strategy makes use of a probability sampling process. The method of choice is straightforward random sampling. The sample for this study will consist of 100 respondents in total. Questionnaires and literature reviews were the modalities of data gathering employed in this study. The chosen method of research for this study will be quantitative research. The research methodology employed in this study is path analysis. The following conclusions were drawn from the analysis's findings: first, the e-service quality variable directly influences judgments. The trust factor is similar in that it likewise directly affects choices. Second, factors related to e-service quality and trust have a big impact on judgments at the same time. Third, decision variables, trust, and the quality of e-services all have a direct impact on customer happiness. Fourth, customer happiness is significantly impacted by decision variables, e-service quality, and trust all at the same time. Fifth, through decisions to utilize e-money services, there is an indirect relationship between e-service quality and trust and consumer happiness. Therefore, the quality of electronic services, the level of consumer trust, and purchasing decisions significantly shape consumer satisfaction, both directly and through indirect influences. These results provide an in-depth look at the factors influencing consumer decisions and satisfaction in the context of e-services.